Disoriented disciplines : China, Latin America, and the shape of world literature - Hubert, Rosario (FlashPoints (Evanston, Ill.), 2024)
"This is a study of the archival formations, theoretical debates, and geopolitical frameworks that constructed an idea of China in Latin America from the nineteenth century to the present"--